A comparative and systems approach to banana cropping systems in the Great Lakes region - Damme, J. van; Bouver, D. de; Dupriez, M.; Asten, Piet J.A. van; Baret, P.V. (CAB International, 2013)
To explore the diversity and efficiency of smallholder farms, we developed an approach based on a comparative framework and a systems analysis, Five sites in three countries (Rwanda, Burundi and Democratic Republic of Congo) were studied in parallel to take account of variations in agro-ecological and institutional conditions. In a systems-based perspective, we used a combination of quantitative (field measurements, economic valuation) and qualitative methods (semi-directed interviews) to capture the diverse nature of smallholder cropping systems. The novelty of the approach is that qualitative dimensions are included in the farm-level diagnostics, while maintaining a comprehensive and reproducible tool for systems analysis in terms of performance, constraints and drivers. The highest productivity in terms of annual revenue/ha was observed in the medium-sized farms (0.7-1.0 ha). It was also in this category that the number of crops cultivated was the greatest. Our hypothesis is that this high efficiency is the outcome of a system '\There productivity and risk management are optimized.